Immunomodulatory Plant Natural Products as Therapeutics against Inflammatory Skin Diseases - Sampath Kumar, Nikhila; Reddy, Navaneetha; Kumar, Halmuthur; Vemireddy, Sravanthi (Current Topics in Medicinal Chemistry, 2024)
Frequently occurring inflammatory skin conditions such as psoriasis, dermatitis, acne, including skin cancer, wounds and other disorders arising out of premature skin aging, deteriorate skin health and adversely impact human life. Even though several synthetic compounds have evolved for treating these skin conditions, natural-product-based therapeutics are gaining popularity with growing evidence of their efficacy and safety for treating skin disorders. Many of these inflammatory skin diseases have underlying disturbances in our immune system and immunomodulatory natural products provide solutions for their effective treatment and aid in understanding the underlying mechanism of such inflammatory skin conditions. Based on this premise, the present review summarizes the possible application of plant-derived immunomodulatory compositions and single molecules for treating inflammatory skin conditions. In vitro, in vivo and mechanistic studies reported the application of selected plant-derived natural products for the treatment of inflammatory skin disorders including, cancer and infections. Several online databases including PubMed, Google Scholar, and Science Direct have been searched for gathering the information covered in this review. Empirical studies demonstrated that most of these natural compounds exhibited therapeutic properties through their immunomodulatory and anti-inflammatory potential supplemented often with anti-microbial, anti-neoplastic, and anti- oxidant activities. Overall, plant-based natural products discussed here are capable of modulating the immune system to minimize or completely suppress the pro-inflammatory markers, scavenge free radicals (ROS), prevent bacteria, fungal, and virus-derived skin infections and often regress skin cancer through the induction of apoptosis. The challenges and opportunities associated with the application of plant-based immunomodulators for skin applications and their safety considerations are also discussed here. The present study indicated that immunomodulatory plant natural products being biologically validated ligands against various biological targets manifested in inflammatory skin diseases, offer an effective, safe and affordable treatment for such disorders affecting skin health. However, further clinical evaluations are needed to substantiate these findings.
Keywords: Immunomodulators